Green Policy Divergence In The Developing World: The Nexus Of Energy, Finance, And Religious Affiliation - Basri, Basri; Akmal Asman; Yusuf Rahim; Yusri, Yusri (ORGANIZE: Journal of Economics, Management and Finance, 2026)
This study assesses the impact of energy, fiscal, monetary, green economy, and ICT policies on carbon emissions. Using a dynamic GMM estimator, it analyzes panel data from 38 OIC and 81 non-OIC developing countries from 2012 to 2021. The findings reveal divergent policy impacts: while renewable energy reduces emissions, fossil fuel use also shows an emission-lowering effect, potentially through efficiency gains. Conversely, electricity consumption increases emissions. In fiscal policy, tax revenue correlates with higher emissions, whereas government spending and industrial activity suppress them. Paradoxically, key green economy indicators the human development index and forest cover are associated with increased emissions, alongside the effects of ICT development. These complex results underscore the need for nuanced, integrated policy design. The study concludes that a strategic policy mix harmonizing fiscal, energy, and technological interventions is crucial for developing nations to achieve sustainable, green economic growth and contribute effectively to global climate mitigation.